Diffuser design and experiment on a stratified chilled-water storage tank - 赵军; 余乐渊; 宋佳钫; 李新国; 朱强 (Zhileng xuebao)
This papers analyses the factors affecting the diffuser design in a stratified chilled-water storage tank,and the diffuser is one of most important factors.So introduces the design principles and basic assumptions of diffuser.The diffuser was designed on an example and taken experiments on a laboratorial stratified chilled-water storage tank in 110 minutes.By testing the diffuser,the stratfied chilled-water storage tank can work efficiently and economically with the requirement of the chiller's design characteristics.